PENGEMBANGAN KEREATIVITAS MASYARAKAT MELALUI HASIL KARYA TENUN DI DAERAH SA’DAN, TORAJA UTARA - Lani Anjaya Banne; Megi Pasolang, Welsi, Sridayanti Ratte Tasik, Theresia Duma (ADISAM PUBLISHER, 2025)
Corona Virus Disease (Covid 19) which has hit the world, including Indonesia, has caused a lot of unrest among the public. Some of these concerns can be seen from the number of activities and jobs that cannot be carried out as usual which then makes people's incomes decrease. As a result, the economic needs of the community have also decreased. To solve this problem, it is important to take action as a form of fulfilling the economic needs of the community. The method used by the author is using a descriptive approach, and ethnographic research studies. Collecting data related to people's lives in the village of Sa'dan sub-district, especially on economic problems due to the covid 19 outbreak by encouraging the community to use various handicrafts with the aim of meeting the needs of people's lives during the pandemic. As for some of the activities that can be carried out by the community as a form of handicrafts, namely: weaving works that can be sold at an adequate price, natural management by planting vegetables to meet economic needs, and raising livestock. Activities like this are not only carried out to fulfill the necessities of life, but are also activities that can provide benefits to the community to learn to develop the potential that God has given and learn to love nature as a gift from God. From the results of the study, the creativity of the people in the Sa'dan area in the form of weaving work has become a habit carried out by the people in that place as a job that is done at home to meet the needs of the community's economic life